You Are What They Eat: The Influence of Reference Groups on Consumers’ Connections to Brands - Escalas, Jennifer Edson; Bettman, James R. (Journal of Consumer Psychology, 2003)
The set of associations consumers have about a brand is an important component of brand equity. In this article, we focus on reference groups as a source of brand associations, which can be linked to one's mental representation of self to meet self‐verification or self‐enhancement goals. We conceptualize this linkage at an aggregate level in terms of self‐brand connections, that is, the extent to which individuals have incorporated a brand into their self‐concept. In 2 studies, we show that brands used by member groups and aspiration groups can become connected to consumers’ mental representation of self as they use these brands to define and create their self‐concepts. Results from Experiment 1 show that the degree to which member group and aspiration group usage influences individual self‐brand connections is contingent on the degree to which the individual belongs to a member group or wishes to belong to an aspiration group. In Experiment 2, we found that for individuals with self‐enhancement goals, aspiration group brand use has a greater impact on self‐brand connections; for individuals with self‐verification goals, on the other hand, member group use has a greater impact.